Genotype x Environment x Management (GEM) Reciprocity and Crop Productivity - Mahmood, Tariq; Ahmed, Talaat; Trethowan, Richard (Frontiers in Agronomy, 2022)
Human population growth requires food production to increase at a matching pace. Crop productivity largely depends on GEM reciprocity and variation in any factor may potentially alter the overall response. Introduction of improved cultivars causes interactive responses within the farming system which may produce tangible benefits only in the presence of suitable environments and management practices. The yield gap which is defined as the difference between yield potential and average farm yield varies in extent among regions ranging from moderately high to alarmingly high. Variation in environments and management practices impacts both the quantity and quality of produce. The highest gains can be achieved if factors in the interaction model work complementarily. System efficiency indicators are useful for assessing the overall system performance. In the face of new challenges plant breeding is receptive to shifts in objectives and strategy. Extension experts are trained to transfer technology and help farmers optimise for better gains. The extension service is also crucial for feedback to researchers. Better crop management has helped realize the genetic potential of crop cultivars in specific settings. Once a productivity plateau has been reached following optimization of management practices for specified environments, then further improvement of the system can be attained through new genetic interventions. For higher productivity a stronger linkage among researchers, extension experts, and farmers is vital. To help the decision support systems GEM interactions need precise scientific analysis and interpretation. A general account rather than a specific view on GEM reciprocity is presented.